THE COMPARISON OF CONCEPTS BETWEEN FUTUWWAH IN THE DISCIPLINE OF SUFISM WITH FITUA IN BIMA SUFISM EAST INDONESIA. - Hendrawangsyah, Hendrawangsyah; Omar, Syed Hadzrullathfi Bin Syed Omar (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2022)
The people of Bima only know Fitua as a tradition—which some Muslim groups use Fitua as a forum or space for interpreting Islamic values ??through religious philosophy discourse with one term "ngaji tua", as well as a space for deepening practice worship at the level of essence (haqiqah). This article attempts to trace and re-identify texts in the discipline of Sufism that are related to Fitua. Considering that the text does not stand alone, the study of this article is also built on the assumption that every text is a mosaic; absorption quotations, and the transformation of other texts, so that the new text allows for absorption and transformation of the previous text. The author places Fitua as a new text, then reads it and relates it to the concept of Futuwwah as the previous text to find the relationship between the two. Through qualitative descriptive research, this article explains as deeply as possible the relationship between Fitua as Bima Sufism and the concept of Futuwwah as one of the disciplines of Sufism. From the results of this interpretation and analysis, this article is able to show that Fitua is a local Islamic spiritualism (Sufism) of Bima with the concepts and teachings of Futuwwah which was built based on the advice of Maja labo Dahu with the five pillars of the life principles of the Bima Muslim community, namely maja, 'dahu, su'u sawa'u sia sawale, ngahi rawi pahu, and toho mpara nahu, sura dou labo dana—as a way (tareqah) in Sufism